Terceira cabaça de Exu: análise dos sentidos sobre gênero e sexualidade nos currículos dos cursos de Pedagogia das universidades brasileiras - Ferreira, Isabella Rocha Azevedo (Universidade do Vale do Rio dos Sinos, 2025)
What meanings about gender and sexuality are conveyed and constructed in the curricula of Pedagogy courses at Brazilian universities? In what ways do these meanings cross over and shape the training paths of future teachers? These questions guided this research. To answer them, we used and articulated the concepts of gender, sexuality, curriculum, teaching, power and truth, from the theoretical fields of Gender Studies, Sexuality Studies, Curriculum Studies, Teaching Studies and Foucauldian Studies. The methodological procedure chosen was documentary research, as we understand that documents are not just a record of the past, but a product of the society that produced them — voluntarily or involuntarily — crossed by power relations (Le Goff, Jacques, 2013). The documents were produced by the author by systematizing the subjects that mention gender and/or sexuality in their titles in Pedagogy courses at Brazilian public, community and private universities. We also used the research found in the literature review, which dialogues with the aforementioned empirical material. To select the universities, a search was carried out in the National Council for Scientific and Technological Development repository of research groups, using the descriptors “gender” OR “sexuality” and the filter by area of Education, in which 66 universities and 39 academic activities were mapped. After analyzing the documents based on the research questions, two processes of regulation of gender and sexuality in the curricula of Pedagogy courses were identified, and a third movement of deregulation. These three processes make up the thesis defended in this research on the three gourds of Exu. At the same time, gaps were analyzed that indicate the progress that universities have made in introducing and working on gender and sexuality in conjunction with curricula.This defends the thesis that these three processes can be understood as a tidal movement, in which we can see retreats, setbacks, as well as advances and directions that we can't measure or predict; the waves may occupy a small part of the sand, but they can also operate in a grandiose way. This process of deregulation through the gaps is called “the third gourd of Exu”, inspired by an itan (in this dissertation, told by Linn da Quebrada), that Exu received two gourds, one with good and one with evil, and mixed them to be poison and to heal. The research thesis is also anchored in the following theoretical foundations: “teaching humanity” (Dal’Igna, 2023); “teaching as an offering” (Dal’Igna, 2024d); “curriculum” (Silva, Tomaz da, 2007a); and, the power of the guardian people (Peixoto, Norberto, 2019). In this research, the analyses may also indicate that Exu forms the third gourd, breaking with the idea of good and evil. It is argued that we should not look at empirics in a negative way, as if there were no advances in curricular matrices, but that we should look for a third way, that we should look at these processes critically, which this dissertation calls the third gourd of Exu.
Keywords: Currículo; Pedagogia; Formação de professores; Gênero; Sexualidade; Curriculum; Pedagogy; Teacher training; Gender; Sexuality; ACCNPQ::Ciências Humanas::Educação